Advanced Technical Considerations for Implanting the t-Branch Off-the-Shelf Multibranched Stent-Graft to Treat Thoracoabdominal Aneurysms. (August 2018) - Ferreira, Marcelo; Ferreira, Diego; Cunha, Rodrigo; Bicalho, Guilherme; Rodrigues, Eduardo
Purpose: To demonstrate different techniques and device modifications that can expand the anatomic suitability of the off-the-shelf multibranched t-Branch for treatment of thoracoabdominal aortic aneurysm.Technique: The t-Branch device is not customized for specific patient anatomy, and the most frequent limitations to its use are an inadequate sealing zone and renal artery anatomy. Experience with this device has prompted the development of several techniques that can be employed to maximize the suitability of this stent-graft. Advice is offered on modification of the device to minimize the risk of paraplegia or better match patient anatomy. Maneuvers are explained to ease delivery through tortuous anatomy or existing stent-grafts, catheterize visceral target vessels, select a bridging stent, reduce ischemia time in the limbs, and alter the configuration of the branches.Conclusion: Employing adjunctive maneuvers can increase the anatomic suitability of the t-Branch; in our experience, these techniques have increased the applicability to more than 80% of all elective and urgent thoracoabdominal aortic aneurysm cases.